Nesidiocoris tenuis, Macrolophus pygmaeus (Hemiptera: Miridae) and (Z)‑3‑hexenyl propanoate induce systemic resistance against the root‑knot nematode Meloidogyne spp. in tomatoes - Fullana, Aida Magdalena; Giné, Ariadna; Urbaneja, Alberto; Pérez-Hedo, Meritxell; Sorribas, Francisco José; Expósito, Alejandro (Springer, 2025)
The management of Meloidogyne spp. in tomato crops presents significant challenges for sustainable agriculture. This study evaluates the potential of Nesidiocoris tenuis, Macrolophus pygmaeus, and (Z)-3-hexenyl propanoate—two zoophytophagous mirid species and one of the herbivore-induced plant volatiles (HIPVs) they trigger—to induce systemic resistance against Meloidogyne incognita and M. javanica in tomato plants (cv. Bodar). To this end, we assess the expression of the PIN2 and PR1 genes, related to the jasmonic acid (JA) and salicylic acid (SA) pathways, respectively. Exposure of tomato plants to 15 nymphs of either N. tenuis or M. pygmaeus for 24 or 48 h, and to (Z)-3-hexenyl propanoate for 24 h, before inoculation with 200 secondstage juveniles of the nematodes significantly reduced nematode infectivity and reproduction. Notably, PIN2 gene expression in leaves was upregulated nine- and 14-fold by N. tenuis and M. pygmaeus, respectively, zero days after nematode inoculation (DANI) and was repressed by the nematode seven DANI with a ninefold decrease, but not when the plants were exposed to M. pygmaeus or N. tenuis, indicating a strong early defense response. However, PR1 expression levels showed no significant changes, suggesting a predominant role of the JA pathway over the SA pathway in the induced resistance. We conclude that induction of systemic resistance in tomato plants by N. tenuis, M. pygmaeus, and (Z)-3-hexenyl propanoate before nematode exposure is a promising strategy for nematode management, at least to suppress nematode infection by the primary inoculum and later reproduction.